THE ROLE OF NATIONAL TRADITIONS AND VALUES IN MORAL EDUCATION OF PRESCHOOL CHILDREN (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article describes the formation of national traditions and values in moral education of preschool children. The role of moral education in raising children as a mature person and the importance of inculcating our universal traditions and values into children’s minds by giving them moral education have been shown. The role of educators and pedagogues in the formation of national traditions and values by providing moral education to the young generation was discussed.